The Affect of Accounting conservatism on Financial Performance-Empirical Study on Companies Listed in Damascus Stock Exchange- - حيدر , فادي; حاتم, إياد; محمد, نذير (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The study aimed to determine the effect of accounting conservatism, measured by the accruals on financial performance, as measured by three indicators: return on assets, Tobin Q, and earning per share. To achieve that aim; Secondary data is collected from the annual financial reports of the companies listed on the Damascus Stock Exchange, which are available on the official website of that market. The study used cross-sectional data, and the data was analyzed using the Eviews 10 program. Between the pooled regression model, the fixed effects model, and the random effects model, it was also confirmed that the normal distribution of the residuals was tested. The number of these companies reached 19 during the period from 2013 to 2020, with a total of 152 views. The results showed that there is an effect of accounting conservatism on each of the return on assets, return on equity, and stock returns. The results showed that there is significant effect of accounting conservatism on the financial performance, this effect is negative for return on assets and earning per share, while the results showed that relationship is a positive effect for the , Tobin Q.